2020
DOI: 10.1088/1572-9494/ab7708
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic moments of odd-Aaluminum isotopes in covariant density functional theory

Abstract: The ground-state properties, especially the magnetic moments, of odd-A aluminum isotopes have been studied and well reproduced in covariant density functional theory after considering the rotational coupling. The present calculations support the rotational structure in the ground state of odd-A aluminum isotopes, i.e. the ground state is built on the intrinsic state 5/2[202]. In addition, the contribution from the time-odd fields is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Eventually, it was found that the deviation is contributed by the effects of a two-body meson exchange current (MEC, i.e., the exchange of the charged mesons) and configuration mixing (CM, or core polarization, i.e., the correlations beyond the mean field approximation) [7,14,15]. With these two corrections, the magnetic moments of odd-even nuclei around doubly magic nuclei can be reproduced well in both non-relativistic and relativistic frameworks [7,[16][17][18][19][20][21][22][23][24]. For odd A nuclei far from the magic nuclei, the effective spin and orbital g factor are usually adopted in different promising theoretical models [25], and are even applied for certain specific nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, it was found that the deviation is contributed by the effects of a two-body meson exchange current (MEC, i.e., the exchange of the charged mesons) and configuration mixing (CM, or core polarization, i.e., the correlations beyond the mean field approximation) [7,14,15]. With these two corrections, the magnetic moments of odd-even nuclei around doubly magic nuclei can be reproduced well in both non-relativistic and relativistic frameworks [7,[16][17][18][19][20][21][22][23][24]. For odd A nuclei far from the magic nuclei, the effective spin and orbital g factor are usually adopted in different promising theoretical models [25], and are even applied for certain specific nuclei.…”
Section: Introductionmentioning
confidence: 99%